Achievements and Contributions in the Field of Partial Differential Equations: Special Issue Dedicated to Academician Zhou Yulin’s Centenary Birthday (Journal of Partial Differential Equations, 2023)
Professor Zhou Yulin was born on February 12, 1923 in Shanghai and passed away onMarch 2, 2021 in Beijing. As a famous mathematician, he was the deputy director of theInstitute of Applied Physics and Computational Mathematics, a member of the Scienceand Technology Committee of the Chinese Academy of Engineering Physics, and thechairman and honorary chairman of the Chinese Society of Computational Mathematics.